The Meanings of AL-Maa’ in AL-Qur’an AL-Kareem - Mohammed Ahmed, Samara (Opción, 2019)
To know the meaning of a word means to know its meaning and the context in which a word is used to express a particular meaning of a word knowledge. In the case of polysemous signs, a word is said to have more than related mean- ing. So, the role of the context in this case is to determine the exact meaning, to resolve potential ambiguities and to identify the intended meaning of such of such polysemous words. As a result, the context is an extra linguistic feature which always comes first to direct the process of getting the exact meaning of the polysemous word”AL-Maa’”from the beginning of this paper. The problem of this study arises at the level of word meaning of the word “AL- Maa’” in AL-Qur’an AL-Kareem as a polysemous word. Also , the problem arises in the following points: 1- Why polysemy is a source of anambiguity ,a problem and confusion in meaning. 2- There is no simple means to identify the different senses of a word. 3- The difference between polysemy and homonymy. 4- The role of the context in solving such am ambiguity. This study aims at investigating the problem of recognizing the suitable pol- ysemous words in order to produce coherent texts meaning of the word AL- Maa’ in AL-Quraa’n AL-Kareem. Also this study intends to shed light on one of the lexical problems (i.e. polysemy)which affect the meanings of this word (i.e.AL-Maa’)in different texts and to get the exact meaning at any text. The analysis of the data collected revealed that the problem of polysemous words give rise in this study especially of the word AL-Maa’’ which is taken as a form of polysemous word that will appear in many contextualized sen- tences of about (23)texts from AL-Quraa’n AL-Kareem. These texts are taken to show the different meanings of this word and the role of context to specify its meanings in this study.